2018
DOI: 10.29333/ejgm/81730
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, fibrinolytic and cytokines parameters response to weight reduction in obese subjects

Abstract: Background: Obesity is a major risk factor for developing cardiovascular disorders due to increased platelets count and platelets activation. Objective: The aim of this study was to measure the influence of weight loss on the coagulation and fibrinolysis parameters among obese patients. Material and Methods: One hundred obese subjects of both genders (mean age 46.72± 3.13 year) selected from the Internal Medicine Department at King Abdul Aziz University Teaching Hospital, their body mass index (BMI) ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The findings have indicated that regular aerobic exercise significantly regulates homeostasis by reducing precoagulation factors and increasing anticoagulation factors 44 , 45 . Possible related mechanisms are that aerobic exercise enhances vascular endothelial integrity, vascular permeability, and the release of vasodilators [46] , such as nitric oxide, which induces the release of tissue plasminogen activator (tPA) from endothelial cells 46 , 47 and suppresses plasminogen activator inhibitor type 1 (PAI-1) production by vessels and platelets [46] . An inverse correlation has been shown between physical activity and TF (factor VIII) 48 , 49 , and factor VII decreases in sedentary men following three months of aerobic exercise training [48] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings have indicated that regular aerobic exercise significantly regulates homeostasis by reducing precoagulation factors and increasing anticoagulation factors 44 , 45 . Possible related mechanisms are that aerobic exercise enhances vascular endothelial integrity, vascular permeability, and the release of vasodilators [46] , such as nitric oxide, which induces the release of tissue plasminogen activator (tPA) from endothelial cells 46 , 47 and suppresses plasminogen activator inhibitor type 1 (PAI-1) production by vessels and platelets [46] . An inverse correlation has been shown between physical activity and TF (factor VIII) 48 , 49 , and factor VII decreases in sedentary men following three months of aerobic exercise training [48] .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the interventions ranged from 3 weeks to 52 weeks (Table 1). From the 37 studies, 27 looked at the impact of caloric restriction on obese patients [26,27,29,31,, 4 in patients with type 2 diabetes mellitus (T2DM) [40,41,45,53], 3 in patients with metabolic syndrome [46,48,59] and 1 in postmenopausal women [44]. Multiple variations of calorie restriction diets were used in the included papers ranging from very low-calorie diets (VLCD) to the Mediterranean diet and lowfat diets.…”
Section: Study Characteristicsmentioning
confidence: 99%